47.4k views
3 votes
Given the expression 12 over 12 to the third power.

Part A: Explain how the Quotient of Powers was used to simplify the expression

Part B: Simplify the expression

User Dror
by
6.3k points

2 Answers

0 votes
Part A: You can subtract the exponents 1 and 3 to end up with 12^-2. Then, you can simplify it into a fraction.

Part B: 12 ^ -2 = 1 / (12^2) = 1 / 144 OR about 0.007
User Abu Aqil
by
6.2k points
5 votes
Part 1:
Before we begin, you need to remember the following rule:

(x^a)/(x^b) = x^(a-b)

The given expression is:

(12)/(12^3)

Since the base is the same in both numerator and denominator, we can apply the above rule. This means that:

(12)/(12^3) = 12¹⁻³ = 12⁻²

Part 2:
Before we begin, you need to remember the following rule:
x⁻ᵃ =
(1)/(x^a)

Now, from part 1, we simplified the expression into 12⁻²
Since the power is negative, we can apply the above rule.
This means that:
12⁻² =
(1)/((12)^2) = (1)/(12*12) = (1)/(144)

Hope this helps :)
User Pramuka
by
5.7k points